Combined ground-based optical support for the aurora (DELTA) sounding rocket campaign - Griffin, E; Kosch, M; Aruliah, A; Kavanagh, A; McWhirter, I; Senior, A; Ford, E; Davis, C; Abe, T; Kurihara, J; Kauristie, K; Ogawa, Y (TERRA SCIENTIFIC PUBL CO, 2006)
The Japan Aerospace Exploration Agency (JAXA) DELTA rocket experiment, successfully launched from Andoya at 0033 UT on December 13, 2004, supported by ground based optical instruments, primarily 2 Fabry-Perot Interferometers (FPIs) located at Skibotn, Norway (69.3 degrees N, 20.4 degrees E) and the KEOPS Site, Esrange, Kiruna, Sweden (67.8 degrees N, 20.4 degrees E). Both these instruments sampled the 557.7 nm lower thermosphere atomic oxygen emission and provided neutral temperatures and line-of-sight wind velocities, with deduced vector wind patterns over each site. All sky cameras allow contextual auroral information to be acquired. The proximity of the sites provided overlapping fields of view, adjacent to the trajectory of the DELTA rocket. This allowed independent verification of the absolute temperatures in the relatively quiet conditions early in the night, especially important given the context provided by co-located EISCAT ion temperature measurements which allow investigation of the likely emission altitude of the passive FPI measurements. The results demonstrate that this altitude changes from 120 km pre-midnight to 115 km post-midnight. Within this large scale context the results from the FPIs also demonstrate smaller scale structure in neutral temperatures, winds and intensities consistent with localised heating. These results present a challenge to the representation of thermospheric variability for the existing models of the region.